HERMENÉUTICA JURÍDICA EN LA PANDECTISTICA ALEMANA. ESPECIAL ATENCIÓN A LA RECHTSLEHRE DE GEORG FRIEDRICH PUCHTA. - GARRIDO MARTÍN, JOAQUÍN (Anales de la Cátedra Francisco Suárez, 2019)
The text approaches the renewed legal hermeneutics of the early German nineteenth century, an anti-code, anti-natural law place and period: a "historicist" one (geschichtlich). Adjectives of a legal century with a positive law that does not create the legislator, but that is inheritance of the past, ratio scripta: "present" Roman law or heutiges römisches Recht. Among the "legal" strategies used at the time to legitimize the validity of the old Roman law, above all one is here of interest: the legal interpretation. Legal hermeneutics is reborn as the historical mentality is introduced in the field of the sciences of the spirit (Geschichtswissenschaften). But a close approach to the "pandectistic" idea of interpretation, based on the texts of the authors of this movement, belies the "conceptualist" vision that is normally associated with the period of the famous Begriffsjurisprudenz. In the revision of this traditional vision we analyse the particular case of Georg Friedrich Puchta, successor of the great Savigny. The "heutiges" Roman law, to become "present", had to be modified in what according to the needs of the Volksgeist was necessary, and the interpretation work of the jurist teaches sometimes a constructive work that is not coherent with the "formalism" that the traditional historiography attributes to the legal science of the Historical School of Law.